Proton conduction in a hydrogen-bonded complex of copper(II)-bipyridine glycoluril nitrate - Tayade, Sakharam B.; Dhavale, Vishal M.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Loennecke, Peter; Hey-Hawkins, Evamarie; Pujari, Bhalchandra (Dalton Transactions, 2017)
Bipyridine glycoluril (BPG), a urea-fused bipyridine tecton, forms a square-pyramidal secondary building unit with copper(II) which further self-assembles to give a porous hydrogen-bonded complex. This complex displays a high proton conductivity of 4.45 x 10(-3) S cm(-1) at 90 degrees C and 95% relative humidity (RH). Chains consisting of coordinated water, solvent water and nitrate anions embedded in the complex are responsible for high proton conduction. The proton conduction pathway was corroborated by ab initio electronic structure calculations with molecular dynamics (MD) simulations using the Nudged Elastic Band (NEB) method. The theoretical activation energy estimated to be 0.18 eV is in close agreement with the experimental value of 0.15 eV which evidences a Grotthuss proton hopping mechanism. We thus demonstrate that the hydrogen-bonded complex encapsulating appropriate counter ions, coordinated water and solvent water molecules exhibts superprotonic conductivity.

Water mediated proton conductance in a hydrogen-bonded Ni(II)-bipyridine-glycoluril chloride self-assembled framework - Tayade, Sakharam B.; Bhat, Satish S.; Illathvalappil, Rajith; Dhavale, Vishal M.; Kawade,Vitthal A.; Kumbhar, Avinash S.; Kurungot, Sreekumar; Näther, Christian (CrystEngComm, 2018)
Proton conducting properties have been investigated in a new Ni(II)-based hydrogen-bonded porous framework synthesized using a urea-fused bipyridine-glycoluril (BPG) tecton. This hydrogen-bonded self-assembled structure encapsulates water molecules in the channels with hydrogen-bonding networks which exhibits a significant temperature dependent proton conductance of 1.5 × 10−4 S cm−1 at 95 °C and 95% RH with a low activation energy (Ea) of 0.54 eV, implying a Grotthuss proton hopping mechanism mediated by hydrogen-bonded water molecules in the channels. In addition, this framework exhibited a very high water uptake under humid conditions. A continuous array of water molecules and chloride ions embedded in the highly hydrophilic porous channels of the hydrogen-bonded framework acts as the proton conducting medium.

A copper(ii)-coordination polymer based on a sulfonic-carboxylic ligand exhibits high water-facilitated proton conductivity - Tayade, Sakharam B.; Illathvalappil, Rajith; Lapalikar, Vaidehi; Markad, Datta; Kurungot, Sreekumar; Pujari, Bhatchandra; Kumbhar, Avinash S. (Dalton Transactions, 2019)
Proton conduction ability has been investigated in a new Cu(ii) based coordination polymer (CP), {[Cu-2(sba)(2)(bpg)(2)(H2O)(3)]center dot 5H(2)O}(n) (1), synthesized using the combination of 4-sulfobenzoic acid (4-Hsba) and bipyridine-glycoluril (BPG) ligands. Single crystal X-ray structure determination revealed that 1 features 1D porous channels encapsulating a continuous array of water molecules. Proton conductivity measurements reveal a high conductivity value of 0.94 x 10(-2) S cm(-1) at 80 degrees C and 95% RH. The activation energy (E-a) of 0.64 eV demonstrates that the solvate water, coordinated water and hydrophilic groups in the channels promote the mobility of protons in the framework. Water sorption measurements exhibited hysterical behaviour with a high uptake value of 379.07 cm(3) g(-1). Time-dependent measurements revealed that the proton conductivity is retained even after 12 h of measurements. The proton conduction mechanism was validated by ab initio electronic structure calculations using the Nudged Elastic Band (NEB) method with molecular dynamics (MD) simulation studies. The theoretical activation energy is calculated to be 0.54 eV which is in accordance with the experimental value.